1996
DOI: 10.1007/bf01292620
|View full text |Cite
|
Sign up to set email alerts
|

Brain monoaminergic and neuropeptidergic variations in human aging

Abstract: The effect of age on the monoamines 5-hydroxytryptamine (5-HT), noradrenaline (NA) and dopamine (DA), their metabolites 5-hydroxyindoleacetic acid (5-HIAA), homovanillic acid (HVA), 3,4-dihydroxphenylacetic acid (DOPAC), and the 5-HT precursor 5-hydroxy-L-tryptophan (5-HTP), together with the peptides neuropeptide Y (NPY), somatostatin (SOM), and corticotropin-releasing factor (CRF), was studied in frontal cortex, gyrus cinguli and hypothalamus from 23 healthy control subjects, aged 16-75 years. After correcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 63 publications
1
17
0
1
Order By: Relevance
“…Hypothalamic noradrenaline content has been reported as reduced (Simpkins 1984;Roubein et al 1986) or unchanged (Petkov et al 1987) in aged animals. A recent study in humans reported significant reductions in hypothalamic noradrenaline concentration between 16 to 75 years of age (Arranz et al 1996). Similar developmental changes in whole brain dopamine content have been reported (Coyle 1973;Herregodts et al 1990).…”
Section: J a Hastings · J M Mcclure-sharp · M J Morrissupporting
confidence: 53%
“…Hypothalamic noradrenaline content has been reported as reduced (Simpkins 1984;Roubein et al 1986) or unchanged (Petkov et al 1987) in aged animals. A recent study in humans reported significant reductions in hypothalamic noradrenaline concentration between 16 to 75 years of age (Arranz et al 1996). Similar developmental changes in whole brain dopamine content have been reported (Coyle 1973;Herregodts et al 1990).…”
Section: J a Hastings · J M Mcclure-sharp · M J Morrissupporting
confidence: 53%
“…Factors from the ante-mortem period -in particular, the agonal state and the rapidity of death -as well as the method of tissue preparation and storage, may play greater roles in determining post-mortem yields of nucleic acids and proteins (Yates et al 1990;Harrison et al 1991Harrison et al , 1995Kingsbury et al 1995). While it is now generally accepted that PMI may critically affect the preservation of some brain neuropeptides and catecholamines (Dodd et al 1988;Palmer et al 1988a;Arranz et al 1996), many nucleic acids and proteins are remarkably stable post-mortem (Lukiw et al 1990;Yates et al 1990;Harrison et al 1991;Leonard et al 1993;Ludes et al 1993;Johnston et al 1997;Schramm et al 1999;Yasojima et al 2001;Bahn et al 2002). Similarly, while agonal state does not significantly affect the overall autopsy concentrations of RNA or proteins, it can influence specific transcripts and proteins (Harrison et al 1991).…”
mentioning
confidence: 99%
“…Aging is often accompanied by some alterations in the neurotransmitter systems of humans and other mammals (Arranz et al, 1996;Magnone et al, 2000;Monica et al, 2003). Most of the studies on brain physiology in aging have been performed in rodents and the results do not always show consistent changes in the neurochemical parameters.…”
Section: Discussionmentioning
confidence: 99%